1991
DOI: 10.1164/ajrccm/143.5_pt_1.983
|View full text |Cite
|
Sign up to set email alerts
|

Altitude and Allergy to House-Dust Mites: A Paradigm of the Influence of Environmental Exposure on Allergic Sensitization

Abstract: To further investigate the possibility of a cause and effect relationship between exposure to house-dust mite (HDM) allergens and respiratory disease associated with dust mite sensitivity, we compared schoolchildren living in the Alps, where exposure to HDM is low, with those living at sea level, where it is high. The study included 933 schoolchildren from the fourth and fifth grades. The protocol included the standardized 1978 American Thoracic Society (ATS) questionnaire for children, skin testing using comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
87
2
4

Year Published

1993
1993
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 211 publications
(101 citation statements)
references
References 6 publications
8
87
2
4
Order By: Relevance
“…Considerable research evidence suggests that both indoor and outdoor environmental exposures may be involved in the worldwide increase in asthma (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Some of the strongest associations have been found with indoor allergens such as dust mite and cockroach in children sensitized to that particular allergen (24)(25)(26)(27)(28)(29)(30)(31)(32). Exposure to environmental tobacco smoke, both in utero (15,19) and during childhood (17,18,20), also appears to play an important role in asthma causation and aggravation.…”
Section: Background On Asthma Prevalence Causation and Aggravationmentioning
confidence: 99%
“…Considerable research evidence suggests that both indoor and outdoor environmental exposures may be involved in the worldwide increase in asthma (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Some of the strongest associations have been found with indoor allergens such as dust mite and cockroach in children sensitized to that particular allergen (24)(25)(26)(27)(28)(29)(30)(31)(32). Exposure to environmental tobacco smoke, both in utero (15,19) and during childhood (17,18,20), also appears to play an important role in asthma causation and aggravation.…”
Section: Background On Asthma Prevalence Causation and Aggravationmentioning
confidence: 99%
“…[8] More than half of all dust samples (53.3%) were collected at altitudes below 1500 m. [8] Another study performed at over 1500 m in the Alps found that positive HDM skin test results were significantly fewer in mountain schoolchildren, and the levels of HDM antigens in mattresses were much lower than those at sea level. [7] One study evaluated the prevalence of allergic diseases (rhinoconjunctivitis and asthma) in 3196 children living 3658 m above sea level in Lhasa, Tibet. The prevalence of "wheezing at any time", "diagnosed asthma", and "current wheezing" was 1.4, 1.1, and 0.8% respectively.…”
Section: Degree Of Altitudementioning
confidence: 99%
“…But HA exerts a therapeutic effect in those with allergic airway diseases; the air is fresh, with low levels of pollen and HDMs. [4][5][6][7] The prevalence of pediatric allergic rhinoconjunctivitis and asthma were evaluated (in conformity with the ISAAC Phase III guidelines) at an altitude of 3658 m in Lhasa, Tibet. The frequencies of allergic respiratory symptoms were evaluated in natives (3190 students) who were asked if they "experienced an asthma attack", "were wheezing", and "had asthma"; the prevalence of these conditions was 1.4%, 0.8%, and 1.1%, respectively.…”
Section: Degree Of Altitudementioning
confidence: 99%
See 2 more Smart Citations